Cultural Management in Chile: Between Professionalisation and the Emergence of a Public Intervention Category - Muñoz-Del Campo, N (Taylor and Francis, 2021)
This chapter examines cultural management in Chile from the perspective of public action and takes the skills and knowledge required for working in the field into account. The recent institutional development of Chilean public cultural policy determined educational offerings and, as such, the professional profiles of those in the field. This raises a tension between more administrative approaches and those that are based on learning through practice. In order to have more impact in the region, the chapter argues for an approach that is not limited to economic concerns but incorporates the social and societal peculiarities of the respective country into cultural management education and training. © 2021 selection and editorial matter, Raphaela Henze and Federico Escribal.